IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI PEMERINTAHAN DESA BERBASIS DIGITAL (WEB DESA/KELURAHAN) MELALUI VIRTUAL TRAINING DALAM PELAYANAN PUBLIK MASA PANDEMI COVID 19 DI PROVINSI SULAWESI TENGGARA TAHUN 2020 - Sartono Sartono; La Ode Muhammad Elwan; Adrian Tawai; Muhammad Yusuf; La Ode Aslim (Jurnal Pengabdian NUSANTARA, 2021)
Integrated community service activities (KKN) Thematic Scope of Halu Oleo University aims to contribute to the government and citizens, especially in public services during the Covid-19 Pandemic in Southeast Sulawesi. This activity is a Training on the Use of Digital-Based Village Administration Information Systems (Village / kelurahan Web) in Public Services to Support Physical Distancing in Preventing the Spread of Covid 19 in Southeast Sulawesi Province. The method used in Thematic KKN is carried out online as a form of responding to government policies in preventing and suppressing the spread of Covid 19. Students have activities from the beginning to the end of the KKN activities carried out in their respective domicile areas using the online internet media among others, through mett zoom, WhatShaap, Google Forms, Hosting and website domains. The results of community service activities through Thematic KKN for students provide information that on average, village / kelurahan government officials do not know and understand how to use internet technology facilities in public services, especially the use of digital-based village administration information systems. Only 1 village in Southeast Sulawesi has a website. There has never been any technical training for the village / output website operators. Local government support is very limited in providing village / kelurahan government governance resources online.